MA’HAD DARUL MUTA’ALIMIN SEBAGAI BRANDING MAN 1 BANYUWANGI - Siti Aimah; Eka Lusi Wahyuni (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2022)
The objectives set in this study are: (1) to find out how the implementation of Ma'had Darul Muta'alimin as the branding of MAN 1 Banyuwangi; (2) to find out what are the supporting and inhibiting factors for Ma'had Darul Muta'alimin innovation as the branding of MAN 1 Banyuwangi. Data collection techniques used are observation, interviews, and documentation. The data analysis used is data analysis by Milles and Huberman with the analysis steps, namely: (1) data reduction, (2) data presentation, and (3) drawing conclusions. Meanwhile, the data validity test uses credibility, audibility, dependibility, and confirmability tests. The results of the research: Implementation of Ma'had Darul Muta'alimin as the branding of MAN 1 Banyuwangi, the planning includes: (1) MAN 1 Banyuwangi is a literacy madrasah, (2) the concept of activities, (3) Development of student character, organizing the implementation of ma'had as branding Madrasah include: (1) ustadz who are competent in the field of Islamic religion, (2) measurable and structured activity programs, the implementation of ma'had as madrasah branding includes: (1) preparing the facilities needed by students in ma'had, (2) ma'had 'had as a religious center in madrasah, (3) achievements achieved, (4) direct mentoring of madrasah heads, evaluation of the implementation of ma'had as madrasa branding, including (1) monthly meetings with madrasah heads and ma'had managers, ( 2) external stakeholder meetings, (3) improving the competence of Ustadz Ma'had Darul Muta'alimin.